Do Bando Ao Pcc: A Gestão Da Violência E Seus Desdobramentos Na Sociabilidade Em Paraisópolis - Oliveira, Eduardo Brandao [UNIFESP] (2017)
The favela of Paraisópolis, located between the Morumbi and Vila Andrade neighborhoods, in the city of São Paulo, is often seen as a poor, violent and marginalized area. However, these views are not based on scientific studies. Considering the favela area in the urban environment, I tried to present the transformations that occurred there in the social and urban structure. Above all, those perpetrated by the world of crime and its "norms," which permeate the local sociability. Analyzing the history of Paraisópolis and its social relations one must consider two distinct moments: the time when the favela was dominated by a gang that lost control and power to the PCC in the second moment. This is fundamental to understand how the local life is organized. To study these two moments is to understand a whole network of relationships that permeates the family, the neighborhood, friends and morality posed by this parallel power. In this way, it is possible to see how the old order and the present order are intimately linked to the action of the criminal world and the sociability present there. Therefore, I sought to understand the social relations in Paraisópolis under the aspect of a sociability marked in the past, by an order directly related to unilateral decisions of the gang, through the figure of Old Lourenço, whereas at present, decisions depend on a collective organization, the First Command of the Capital (PCC). Besides, I was able to understand the paths of sociability there and to observe how these relations were renewed over time from one of power to another.